The influence of core service quality associated with Korean women’s volleyball on national image and consumption engagement of Korean products: Perspective of Korean Wave in Thailand - Jeon, Jong-Hwan; Byon, Kevin K.; Song, Hyunseok; Park, Sung-Bae Roger (Frontiers in Psychology, 2022)
Building on the stimulus-organism-response (SOR) framework, we propose and test a hypothesized model of the effect of core service quality on national image and related behavioral intentions (i.e., intention to visit Korea and intention to purchase Korean products). Using 286 samples collected from Nakhon Ratchasima, Thailand, during the Korea-Thai Super Match, we conduct confirmatory factor analysis (CFA) and structural equation modeling (SEM) to examine the measurement model and hypothesis testing, respectively. The results reveal that player attractiveness and emotional experience positively affected national image and behavioral intentions (i.e., intention to visit Korea and purchase Korean products. The findings stress that foreign spectators’ attitudes toward Korean women’s volleyball could translate into consumption behaviors (i.e., visits and Korean products) through the national image.